اختبار الفروق بين معاملات ألفا عبر قياسات التقرير الذاتى والمهام المعرفية لنظرية العبء المعرفى - سليمان، محمود علي موسى (المؤسسة الدولية لآفاق المستقبل, 2020)
اعتمدت الدراسة على تحويلات Feldt (1969, 1980) في استخدام الفروق بين معاملات الفا عبر قياسات المرتبطة عبر قياسات متعددة لنظرية العبء المعرفي. وهدفت الدراسة للمقارنة طبيعة القياس عبر قياسات التقرير الذاتي والمهام المعرفية في إجراء البحوث النفسية والتربوية. واعتمد الباحث على مدخل Peterson (1994) لانتقاء حجم العينة الأمثل والتي بلغت 76 طالب وطالبة من طلاب الفرقة الثانية شعبة علم النفس بكلية التربية بالإسماعيلية ممن يدرسون مقرر الاحصاء النفسي الاستدلالي. وقد اختبر الصدق البنائي للتحقق من العامل العام. وتوصلت النتائج إلى تفوق مقياس التقرير الذاتي في ثباتها وفي قدرتها على إظهار التباين بين أفراد العينة. وأوصت الدراسة بالاعتماد على مقاييس التقرير الذاتي للحكم على السمات المعرفية، وإذا استخدمت المهام المعرفية ينبغي الاعتماد على أداءات تعكس العملية المعرفية في حل المشكلات وتعطى الدرجة على هذه الأداءات في ضوء مقياس ليكرت كمتصل أعلى في تقدير درجة الأداءات.
The study depended on Feldt transformations (1969, 1980) in use of differences between two alpha coefficients across measurements associated with multiple measurements of the cognitive load theory. The study aimed to compare the self-report and cognitive tasks measurements in Psychological and Educational research. The researcher adopted Peterson (1994) approach to select the optimal sample size, which reached 76 students from the 2nd year of the Psychology department at the Ismailia Faculty of Education which studied Psychological inferential statistics. Structural validity had been used to test the common factor structure. The results revealed that self-report scales were superior in their stability and in their ability to show variance among sample participants. The study recommended relying on self-report measures to judge cognitive traits. If cognitive tasks are used, it is necessary to rely on benchmarks that reflect the cognitive process in problem solving. The score on these benchmarks is given in the light of the Likert scale as a higher correlation in estimating the degree of performance.
Keywords: التقارير الذاتية -- المهام المعرفية -- العبء المعرفى